REPLACEMENT COST IN ACCOUNTING VALUATION. - Rorem, C. Rufus (The Accounting Review, 1929)
Replacement-cost is the basic value which properly expresses business capital and income. It is not always easily determined, at times can only be approximated. But even the arguments in favor of other bases of valuation are predicated on the assumption that they are very near to replacement-cost. The replacement-cost of an asset is the estimated expenditure necessary to secure another similar in nature and equivalent in economic value. It frequently is more or less than original cost, usually it varies from sale-price, which is the amount realizable through disposal. The importance of replacement-cost in the balance sheet and the statements of business operations will be illustrated with respect to the accounting entities namely merchandise inventories, fixed assets, trading profit and fixed charges. The replacement-cost of merchandise is the price for which merchandise of similar kind and sales value could be brought into the stock rooms of an enterprise. It is the so-called market-value contemplated in the widely quoted and applied cost-or-market rule of evaluating merchandise inventories.